Keefektivitasan Peran Internal Audit Pada BUMN Era Kabinet Merah Putih - Pangestu, Juan; Simanungkalit, Jobrinson; Hakki, Tandry Whittleliang; Akwila, Karvicha (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
This study aims to identify the factors that influence the effectiveness of internal audit departments in government institutions, particularly in State-Owned Enterprises. The findings of this research are expected to serve as a reference for other auditors at the Audit Board of the Republic of Indonesia to be applied in supervising other government institutions such as local governments, the Financial Services Authority, and ministries under the Merah Putih Cabinet. These efforts are intended to improve institutional effectiveness and reduce the potential for state financial losses. This research examines the effect of audit scope, senior management support, and extrinsic rewards on the effectiveness of internal audits. A quantitative approach was used, and primary data were collected through questionnaires. The research objects were internal auditors from the Audit Board of the Republic of Indonesia involved in auditing State-Owned Enterprises in Jakarta, Bandung, and Surabaya. The sampling technique used was purposive sampling, and hypothesis testing was conducted using multiple linear regression analysis. The results show that audit scope, senior management support, and extrinsic rewards have a significant and positive effect on internal audit effectiveness. These findings indicate that a broader audit scope, stronger management support, and well-targeted rewards contribute to increased internal audit effectiveness. This research contributes to strengthening the oversight system in the public sector by improving the role and quality of internal auditors.